Towards urbanistic geosituation delineation - Serohin, Denys; Kostrikov, Sergiy (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Introduction. Modern cities are complex and rapidly expanding systems. For their more effective study, it is necessary to use methods of urban remote sensing, in particular, LiDAR survey. Processed LiDAR survey data, visualized in a 3D scene, model a certain urban configuration that represents a static picture of the relationships between objects, processes and phenomena in the urban environment. The representation of such configurations in the dynamic plane are urbanistic geosituations. The main research objective of the paper is to define the concept and present the essence of the urbanistic geosituation. Results. The urbanistic geosituation is a dynamic aspect of a certain state of the urban environment, in which there are objects, processes and phenomena that are in dialectical unity with this urban environment. The urbanistic geosituation can be represented as a separate area of the urban environment in a certain research context with a specific state that is currently not inherent in other areas. The article describes in detail the property of the structural heredity of geosituations, which can be traced during the growth of cities. New buildings and roads are laid out taking into account the existing layout, thus inheriting the structure of the original geosituations. On the example of the city of Washington using 2D and 3D maps, the article discusses the features of identifying inherited urbanistic geosituations using the general functionality of visual analysis. On the example of the city of Kharkiv are described urban problems that arise as a result of unplanned development and ignoring the structural heredity of urbanistic geosituations. Repeating geosituations with common properties and internal configurations are combined into different rank geosituational patterns, which are tracked on city maps with the naked eye. The higher the rank of the pattern, the more stable it is, and the larger territories it covers in terms of more generalized properties. The formation of geosituations patterns is successfully combined with the feature of collecting and storing LiDAR data, which are divided into many areas of the same size – tiles. An important property of urbanistic geosituations is their variability, which manifests itself in the city study in the context of the daily population concentration. Diverse internal urban processes and phenomena often lead to the emergence of urbanistic geosituations that characterize the temporary gravity centers of the population. To search, identify and analyze urbanistic geosituations, it is necessary to use two key components – global coverage maps and geographic information systems (GIS). The article describes a special web-GIS that combines these components and provides an environment for exploring urbanistic geosituations in a 3D scene. Three use-cases are also proposed for analyzing urban systems at the geosituational level: visibility analysis, buildings energy consumption estimation, and population estimation [11, 21]. Conclusions. The geosituational approach in urban research can significantly improve the urban environment study. The repeatability of urban geosituations and the small data sets that can be obtained using LiDAR surveys provide grounds for their effective analysis and visualization in GIS, as a result of which it is possible to extract urban geosystem properties that can be relevant for the entire city.